Buffalo Hunt: International Trade and the Virtual Extinction of the North American Bison - Taylor, M. Scott (American Economic Review, 2011)
In the sixteenth century, North America contained 25 to 30 million buffalo; by the late nineteenth century fewer than 100 remained. While removing the buffalo east of the Mississippi took over 100 years, the remaining 10 to 15 million buffalo on the Great Plains were killed in a punctuated slaughter lasting little more than ten years. I employ theory, international trade statistics, and first-person accounts to argue the slaughter was initiated by a foreign-made innovation and fueled by a foreign demand for industrial leather. European demand and American policy failure are jointly responsible for the “Slaughter on the Plains.” (JEL F14, N51, N71, Q57)